2000
DOI: 10.1002/1097-0134(2000)41:4+<23::aid-prot30>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of a unique intra-dimer cooperativity in the human hemoglobin ?1?1half-oxygenated intermediate supports the symmetry rule model of allosteric regulation

Abstract: The contribution of the α1β1half‐oxygenated tetramer [αβ:αO2βO2] (species 21) to human hemoglobin cooperativity was evaluated using cryogenic isoelectric focusing. The cooperative free energy of binding, reflecting O2‐driven protein structure changes, was measured as 21ΔGc = 5.1 ± 0.3 kcal for the Zn/FeO2 analog. For the Fe/FeCN analog, 21ΔGc was estimated as 4.0 kcal after correction for a CN ligand rearrangement artifact, demonstrating that ligand rearrangement does not invalidate previous conclusions regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 96 publications
11
80
1
Order By: Relevance
“…HbS is referred to herein as ''wild type'' with specific reference to its unperturbed dimer-dimer interface contacts. In the case of the doubly ligated species in which both ligands are located on one dimer, the CNmet analog yields an experimental artifact because of ligand exchange, causing this species to have a ⌬G c penalty similar to singly ligated species (5). A correction has been applied to the data shown here for this species, which has no significant effect on the results or conclusions of this study.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…HbS is referred to herein as ''wild type'' with specific reference to its unperturbed dimer-dimer interface contacts. In the case of the doubly ligated species in which both ligands are located on one dimer, the CNmet analog yields an experimental artifact because of ligand exchange, causing this species to have a ⌬G c penalty similar to singly ligated species (5). A correction has been applied to the data shown here for this species, which has no significant effect on the results or conclusions of this study.…”
Section: Methodsmentioning
confidence: 93%
“…. , 4 (in kcal͞mol), for both free dimer (D) and assembled tetramer (Tet) and corresponding tetramer assembly free energies, ⌬G tet, previously determined at pH 7.4 and 21.5°C (5,35). The ligand binding free energy for the free dimer, ⌬G int, also serves as the intrinsic ligand binding free energy for the tetramer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To put the cooperativity in perspective, human I-BABP can be compared with human hemoglobin. The largest cooperativity factor in hemoglobin, which occurs with the binding of the fourth molecule of oxygen, is Ϸ400 (14). For glycocholate binding to human I-BABP, the cooperativity factor exceeds 1,000.…”
Section: Discussionmentioning
confidence: 98%
“…A series of recent findings, however, suggest that, despite this structural equivalence, the ␣ 1 ␤ 1 and ␣ 2 ␤ 2 interfaces are not functionally inert. Ackers et al have demonstrated that, when the second ligand binds to Hb, the microscopic species in which both ligands are on the same ␣␤ dimer is energetically preferred over all other doubly ligated species (8,35). This result implies the existence of favorable cooperativity between ␣ and ␤ hemes within the same ␣␤ dimer, before the T 3 R transition.…”
Section: Allosteric Free Energy Changes At His␣103(g10) and His␣122(hmentioning
confidence: 99%